Molecular static simulations of ferroelectric material hysteresis behaviour - Endres, Florian; Steinmann, Paul (PAMM, 2014)
The present contribution deals with molecular static modelling and the simulation of ferroelectric material hysteresis behaviour. Therefore the core-shell model is implemented in a molecular static algorithm. Moreover the algorithm is implemented as a finite element method for nonlinear trusses. Thereby the computational costs are reduced significantly compared to molecular dynamics. (© 2014 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)
UnivIS-Import:2015-04-17:Pub.2015.tech.FT.FT-TM.molecu_5